2018
DOI: 10.3389/fpls.2018.01374
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Distribution in Annual Growth of ‘Italia’ Table Grape Vines

Abstract: Little information is available about nitrogen (N) content and its concentration in table grape vines. Knowledge of the quantity of N accumulated by the vine organs during the season could support sustainable fertilization programs for table grape vineyards. The aim of the present study was to determine the N content and its concentration in different annual organs, including summer and winter pruning materials, clusters at harvest, and fallen leaves at post-harvest. Specifically, biomass and N were analyzed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…Overall, cover crops slightly modified the grape color, with a more saturated and vivid yellow in the conventional plot, although without compromising the production quality in the cover crop treatment. In fact, the grape colorimetric characteristics observed in the presence of cover crops were in accordance with values usually detected for cv "Italia" grapes produced in the south of Italy [44]. Data reported in the literature about the effect of cover crops on grape color mainly refer to red wine grape varieties [10,39], thus no comparison can be done with our data.…”
Section: Yield and Grape Qualitative Parameterssupporting
confidence: 88%
“…Overall, cover crops slightly modified the grape color, with a more saturated and vivid yellow in the conventional plot, although without compromising the production quality in the cover crop treatment. In fact, the grape colorimetric characteristics observed in the presence of cover crops were in accordance with values usually detected for cv "Italia" grapes produced in the south of Italy [44]. Data reported in the literature about the effect of cover crops on grape color mainly refer to red wine grape varieties [10,39], thus no comparison can be done with our data.…”
Section: Yield and Grape Qualitative Parameterssupporting
confidence: 88%
“…Low N status may be associated with berry growth (Hilbert et al, 2003;Rogiers et al, 2004). Similar to our results, it was reported that in "Italia" ("Bicane"  "Muscat Hamburg") grapevines, the decrease of N content in the primary leaves after flowering indicated a remobilization toward the clusters, which acted as a stronger sink (Ferrara et al, 2018). As "Italia", "New York Muscat" ("Muscat Hamburg"  "Ontario") is a vigorous and woody grapevine that is characterized by clusters of edibles, juicy, sweet, dark maroon to blue-black fruit.…”
Section: Relationship Between Petiole Versus Blade Nutrition Status In Bloom and Véraisonsupporting
confidence: 92%
“…Insufficient N limits vine vigor [6,7]. On the other hand, unnecessary application of N fertilizers needlessly increases the production cost, may cause unintended nutrient imbalances, contributes to environmental contamination [8]), stimulates excess vegetative growth, and reduces grape quality [9]. In fact, excessive application of nitrogen to crop plants has led to significant nitrate groundwater pollution in the SJV [10].…”
Section: Introductionmentioning
confidence: 99%